2020
DOI: 10.3389/fmicb.2020.01971
|View full text |Cite
|
Sign up to set email alerts
|

Type III Secretion Protein, PcrV, Impairs Pseudomonas aeruginosa Biofilm Formation by Increasing M1 Macrophage-Mediated Anti-bacterial Activities

Abstract: Pseudomonas aeruginosa biofilms employ a variety of strategies to hijack the host immune defense system to achieve chronic infection. However, the bacterial components that are involved in this process are not yet fully understood. PcrV, a needle tip protein of the P. aeruginosa type III secretion system (T3SS), was downregulated during P. aeruginosa biofilm infection. The impaired expression of the P. aeruginosa pcrV gene is associated with attenuated immune activation and an increased percentage of M2 macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…During early wound healing, macrophage exhibits an inflammatory phenotype, known as the classically activated M1 macrophage. They act as the first line of defense against pathogen through mainly two ways, namely, recognizing pathogen-associated modifying proteins (PAMPs) on the surfaces of bacteria or fungi to form phagolysosome, and releasing antibacterial mediators, such as reactive oxygen species (ROS) and reactive nitrogen species ( 38 , 39 ). Moreover, they are involved in removal of cellular debris and clearing apoptotic neutrophils ( 40 ).…”
Section: Macrophage Biology In Wound Healingmentioning
confidence: 99%
“…During early wound healing, macrophage exhibits an inflammatory phenotype, known as the classically activated M1 macrophage. They act as the first line of defense against pathogen through mainly two ways, namely, recognizing pathogen-associated modifying proteins (PAMPs) on the surfaces of bacteria or fungi to form phagolysosome, and releasing antibacterial mediators, such as reactive oxygen species (ROS) and reactive nitrogen species ( 38 , 39 ). Moreover, they are involved in removal of cellular debris and clearing apoptotic neutrophils ( 40 ).…”
Section: Macrophage Biology In Wound Healingmentioning
confidence: 99%
“…Compared with the control group, PcrV treatment decreased tumor growth ( Figure 1B ) and weight ( Figure 1C ). We previously demonstrated that PcrV significantly increased NO production in normal BMDMs ( 13 ). Considering that NO-mediated cytotoxicity is associated with tissue apoptosis and the inhibition of tumor growth, we then evaluated the levels of tumor cell apoptosis and the expression of the NO-generating enzyme—iNOS—in PcrV-treated tumor tissues.…”
Section: Resultsmentioning
confidence: 96%
“…These cells showed increased expression of genes related to tumor growth ( Cox2 and Vegfa ), metastasis ( Cox2 , Mmp2 , and Mmp9 ), and immune suppression ( Ido2 ) ( Supplementary Figure 3A ), indicating that TAM generation in vitro had been successful. The levels of tumoricidal M1 polarization markers, including iNos , Cd11c , MhcI , MhcII , Cd86 ( Supplementary Figure 3B ), iNOS ( Supplementary Figure 3C ), NO ( Supplementary Figure 3D ), IL12 p40/70, TNFA ( Supplementary Figure 3E ), MHCII, and CD86 ( Supplementary Figure 3F, G ), were found to be higher in PcrV-primed than mock-treated TAMs, whereas the levels of the protumoral M2 polarization markers c-Myc , Egr2 , Fn1 , Arg1 ( 13 ), and Cd206 were lower ( Supplementary Figure 3B ), demonstrating that PcrV directly reprograms TAMs to an antitumoral M1 profile in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations